The distribution of the DRB4*01:03:01:02N null allele in HLA‐DRB1~DQB1 haplotypes in the Croatian population. (25th December 2017) - Grubic, Z.; Maskalan, M.; Radmanic, L.; Stingl Jankovic, K.; Burek Kamenaric, M.; Zunec, R.
Abstract : The aim of the present study was to investigate frequency and haplotype distribution of DRB4 alleles in the Croatian population. The investigated sample consisted of 288 cadaveric donor samples positive for one of the DR53 alleles. HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 typing was performed using the polymerase chain reaction‐sequence specific primers (PCR‐SSP) low resolution method, while HLA‐DRB4 and selected HLA class II specificities typing was performed using PCR‐SSP at the allelic level. Three different DRB4 alleles were observed among DRB1*04 samples; DRB4*01:02 (2.38%), DRB4*01:03 (91.27%), and DRB4*01:03:01:02N (6.35%). The DRB4*01:03:01:02N allele was predominantly observed among DRB1*04:02 ‐positive samples, while DRB4*01:02 and DRB4*01:03 alleles did not associate preferably with any of the DRB1*04 subtypes. Among DRB1*04~DRB4~DQB1 haplotypes, the predominant DQB1 allele was DQB1*03:02 (69.94%). Seven different DRB4 alleles were found among DRB1*07:01 ‐positive samples. The analysis of DRB1*07~DRB4~DQB1 haplotypes showed that DRB4*01:03 was found in the majority of HLA‐DRB1*07:01~DQB1*02:02 (49.09%) haplotypes while DRB1*07:01~DQB1*03:03 haplotypes carried the DRB4*01:03:01:02N allele almost exclusively (98.21%). Among six DRB1*09:01 ‐positive samples, HLA‐DRB1*09:01~DRB4*01:03~DQB1*03:03 was the only detected haplotype. The extended haplotype analysis showed a high frequency of HLA‐B*15(B62)~C*03(Cw9)~DRB1*04:02~DRB4*01:03:01:02N~DQB1*03:02 and HLA‐B*57~C*06~DRB1*07:01~DRB4*01:03:01:02N~DQB1*03:03 haplotypes. In conclusion, the data presented in this study should prompt other population studies focused on DRB3/4/5 genes and be used as a basis for future investigations of the clinical relevance of these genes in transplantation setting.